Ultrasound-guided pleural puncture in supine or recumbent lateral position: feasibility study - Soldati, Gino; Smargiassi, Andrea; Inchingolo, Riccardo; Sher, Sara; Valente, Salvatore; Corbo, Giuseppe Maria (Multidisciplinary Respiratory Medicine, 2013)
Background: The aim of this study is to evaluate feasibility, safety and efficacy of accessing the pleural space with the patient supine or in lateral recumbent position, under constant ultrasonic guidance along the costophrenic sinus.Methods: All patients with pleural effusion, referred to thoracentesis or pleural drainage from February 2010 to January 2011 in two institutions, were drained either supine or in lateral recumbent position through an echomonitored cannulation of the costophrenic sinus. The technique is described in detail and an analysis of safety and feasibility is carried out.Results: One hundred and one thoracenteses were performed on 76 patients and 30 pigtail catheters were inserted in 30 patients (for a total of 131 pleural procedures in 106 patients enrolled). The feasibility of the procedures was 100% and in every case it was possible to follow real time needle tip passage in the pleural space. Ninety eight thoracenteses (97%) and all catheter drainages were successfully completed. Four thoracenteses were stopped because of the appearance of complications while no pigtail drainage procedure was stopped. After 24 hour follow up, one chest pain syndrome (1.3% of completed thoracenteses) and two pneumothoraces (1.4%) occurred. The mean acquisition time of pleural space was 76 ± 9 seconds for thoracentesis and 185 ± 46 seconds for drainage insertion (p < 0.05).Conclusions: This study highlights the safety and efficacy of this technique of real time echo-monitored pleural space puncture, that offers a more comfortable patient position, an easier approach for the operator, a very low rate of complications with short acquisition time of pleural space.